Implementation of the Flipped Classroom Method in Fiqh Learning at the Riyadotul Badi'ah Prokimal Islamic Boarding School - Ahmad Ahsan Ansori; Supriyanti Supriyanti (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
This study discusses the implementation of the flipped classroom method in Fiqh learning at Riyadotul Badi’ah Prokimal Islamic Boarding School. The flipped classroom is a learning strategy that emphasizes independent study through online and offline materials before face-to-face sessions. The main objective is to enhance students’ participation, learning effectiveness, and deep understanding of Fiqh, which is often considered a complex subject. This research employs a qualitative approach with data collected through observation, interviews, and documentation. The findings reveal that the application of the flipped classroom method positively impacts students’ engagement, critical thinking skills, and learning independence. The challenges encountered include limited technological facilities and students’ readiness to access materials independently. Nevertheless, with the support of the school management and adaptive strategies, this method proves relevant and effective for Fiqh learning in the pesantren environment.